2020
DOI: 10.1038/s41598-020-64981-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screens reveal Escherichia coli genes required for growth of T1-like phage LL5 and V5-like phage LL12

Abstract: The host factor requirements of phages and mechanisms of mutational phage insensitivity must be characterized for rational design of phage cocktails. To characterize host dependencies of two novel Escherichia coli phages, the T1-like siphophage LL5 and the V5-like myophage LL12, forward genetic screens were conducted against the Keio collection, a library of single non-essential gene deletions in E. coli str. BW25113. These screens and subsequent experiments identified genes required by phages LL5 and LL12. E.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…There have been few attempts to use genetic approaches for studying genome-wide host factors essential in phage infection. These loss-of-function (LOF) genetic screens broadly use bacterial saturation mutagenesis [ 49 , 54 , 58 61 ] or an arrayed library of single-gene deletion strains for studying phage-host interactions [ 50 , 51 , 53 , 62 , 63 ]. Consequently, these studies have generally involved laborious experiments on relatively few phages and their hosts, and scaling the approach to characterize hundreds of phages is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…There have been few attempts to use genetic approaches for studying genome-wide host factors essential in phage infection. These loss-of-function (LOF) genetic screens broadly use bacterial saturation mutagenesis [ 49 , 54 , 58 61 ] or an arrayed library of single-gene deletion strains for studying phage-host interactions [ 50 , 51 , 53 , 62 , 63 ]. Consequently, these studies have generally involved laborious experiments on relatively few phages and their hosts, and scaling the approach to characterize hundreds of phages is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Just like the much larger Markadamsvirinae siphoviruses (see below), Drexlerviridae phages use a small set of outer membrane porins as their secondary / final receptors for irreversible adsorption and DNA injection. To the best of our knowledge, previous work had only identified the receptors of T1 and IME18 (FhuA), IME347 (YncD), IME253 (FepA), and of LL5 as well as TLS (TolC) while for an additional phage, RTP, no protein receptor could be identified [40,[52][53][54]. Using available single-gene mutants, we readily determined the terminal receptor of eleven out of our thirteen Drexlerviridae phages as FhuA, BtuB, YncD, and TolC (Figs 4B and 4C) but failed for two others, AugustePiccard (Bas01) and JeanPiccard (Bas02).…”
Section: Properties Of the Drexlerviridae Familymentioning
confidence: 98%
“…Three different, co-expressed lateral tail fibers have been directly visualized in the cryogenic 371 electron microscopy structure of phi92, and large orthologous loci are found in all Vequintavirinae and 372 relatives [23,70,71]. The considerable repertoire of glycan-hydrolyzing protein domains in these tail fiber proteins has been compared to a "nanosized Swiss army knife" and is probably responsible for the exceptionally broad host range of these phages and their ability to infect even diverse capsulated strains of enterobacteria [23,52,70,71]. However, it is far from clear which genes code for which components of the different lateral tail fibers.…”
Section: Properties Of Myoviridae: Vequintavirinae and Relativesmentioning
confidence: 99%
See 1 more Smart Citation
“…A whole-genome BLASTn search (18) indicated that phage U136B is in the Tlsvirus phage group, which includes E. coli bacteriophage TLS (GenBank accession number AY308796.1) (93% identity) and E. coli bacteriophage LL5 (NCBI reference sequence NC_047985.1) (94% identity), both of which are also reliant on the E. coli TolC efflux protein (23,24) and have siphophage morphology with flexible tails (23,25). Host range analysis of phage U136B indicates a limited host range of some, but not all, E. coli hosts (2).…”
mentioning
confidence: 99%